Features of medical and social expertise in ankylosing spondylitis and psoriatic arthritis - T. V. Dubinina; T. V. Korotayeva; A. M. Lila (Современная ревматология, 2023)
Ankylosing spondylitis (AS) and psoriatic arthritis (PsA) are the two most common diseases from the group of spondyloarthritis (SpA), which are often accompanied by permanent disability. Maintaining an acceptable quality of life, preventing the development and progression of structural changes in the musculoskeletal system, maintaining/normalizing functional and social activity are the main goals of their therapy. Over the past decades, the introduction of biological disease modifying antirheumatic drugs has made it possible to achieve significant success in the sustainable control of AS and PsA activity. However, the high cost of treatment significantly limits access to innovative drugs. Specifics of drug supply call for prescription of these drugs in the presence of the status of "disabled", which is assigned on the basis of the results of the medical and social examination (MSE). Execution of the necessary medical documentation for the implementation of the MSE is one of the functions of a rheumatologist.The lecture analyzes the main regulatory legal acts of the Russian Federation regulating the issues of establishing disability and discusses peculiarities of medical reports processing when referring patients with AS and PsA to the MSE.